Special Issue: "Molecular Imaging in Oncology: Radiopharmaceuticals for PET and SPECT 2022" - Junbo Zhang (MDPI AG, 2023)
Molecular imaging is partly defined as in vivo imaging of biological or biochemical processes using various markers [...]